A morphological intermediate between eosimiiform and simiiform primates from the late middle Eocene of Tunisia: Macroevolutionary and paleobiogeographic implications of early anthropoids. Issue 3 (30th April 2014) - Marivaux, Laurent; Essid, El Mabrouk; Marzougui, Wissem; Khayati Ammar, Hayet; Adnet, Sylvain; Marandat, Bernard; Merzeraud, Gilles; Ramdarshan, Anusha; Tabuce, Rodolphe; Vianey‐Liaud, Monique; Yans, Johan
ABSTRACT Although advanced anthropoid primates (i.e., Simiiformes) are recorded at the end of the Eocene in North Africa (Proteopithecidae, Parapithecidae, and Oligopithecidae), the origin and emergence of this group has so far remained undocumented. The question as to whether these primates are the result of a monophyletic radiation of endemic anthropoids in Africa, or several Asian clades colonizing Africa, is a current focus of paleoprimatology. In this article, we report the discovery of a new anthropoid from Djebel el Kébar in central Tunisia, dating from the late middle Eocene (Bartonian). This taxon, Amamria tunisiensis, new genus and species, currently known by only one isolated upper molar, is among the most ancient anthropoids to be recorded in Africa thus far. Amamria displays a suite of dental features that are primarily observed in Eosimiiformes (stem Anthropoidea). However, it is not allocated to any known family of that group (i.e., Asian Eosimiidae and Afro‐Asian Afrotarsiidae) inasmuch as it develops some dental traits that are unknown among eosimiiforms, but can be found in African simiiform anthropoids such as proteopithecids and oligopithecids. With such a mosaic of dental traits, Amamria appears to be a structural intermediate, and as such it could occupy a key position, close to the root of the African simiiforms. Given its antiquity and its apparent pivotal position, the possibility exists that Amamria could have evolved in Africa from Asian eosimiiform or Asian "proto"‐simiiform ancestors, which would have entered Africa sometime during the middle Eocene. Amamria could then represent one of the earliest offshoots of the African simiiform radiation. This view would then be rather in favor of the hypothesis of a monophyletic radiation of endemic simiiform anthropoids in Africa. Finally, these new data suggest that there must have been at least two Asian anthropoid colonizers of Africa: the afrotarsiids and the ancestor of Amamria. Am J Phys Anthropol 154:387–401, 2014. © 2014 Wiley Periodicals, Inc.